Trypsin diminishes the rat potency of polio serotype 3. Issue 6 (November 2015) - ten Have, R.; Westdijk, J.; Levels, L.M.A.R.; Koedam, P.; de Haan, A.; Hamzink, M.R.J.; Metz, B.; Kersten, G.F.A.
Abstract: This study addresses observations made in view of testing in practice the guideline in the European Pharmacopoeia (EP) on omitting the rat potency test for release of polio containing vaccines. In general, use of the guideline is valid and the D-antigen ELISA can indeed be used as an in vitro alternative for the in vivo test. However, the set-up of the ELISA is crucial and should include detection of antigenic site 1 in polio serotype 3 as destruction of that site by trypsin results in a reduced rat potency. Antigenic site 1 in polio serotype 2 may also be modified by trypsin, but the cleavage of viral protein 1 (VP1) did not affect the rat potency. Therefore, any antigenic site, except site 1, can be used for detection of polio serotype 2. It is advised to include testing of the effect of trypsin treatment in the EP-guideline. This allows polio vaccine manufacturers to check whether their in-house ELISA needs improvement.